Influence of biochemicals on regulation of bud break, green leaf yield and crop distribution in tea - Pandey, Renu (Journal of Plantation Crops, 2009)
Tea (Camellia sp.) undergoes winter dormancy for a period of 3 to 4 months in north east India. An attempt was made to hasten the bud break and regulate crop distribution by exogenous application of certain biochemicals viz. Jibika (a commercial mixture of GA3+GA4+GA7), indole-3-acetic acid, cycocel, thiourea, methanol, succinic acid and sucrose besides deionised water as control. It was observed that the bud break was hastened by 11 days and the bushes reached 50% bud break stage by 9.3 days earlier due to Jibika treatment as compared to control. The number of primary shoots (158.0) and dry weight of tipped-in primaries (22.1 g/bush) were the highest in Jibika treated bushes while shoot (25.3 cm) and internodal (4.3 cm) length was maximum in thiourea treated bushes. The mean monthly green leaf yield showed a significant variation due to treatments and the total annual green leaf yield was higher (816.8 g/bush) due to sucrose application. Significant increase was recorded in terms of crop distribution by sucrose treat-ment during early (12.4 %) and mid (18.6 %) season while cycocel treatment produced 27.3 % increase in green leaf during end season with respect to control. Early season crop is important from quality point of view and it was effectively enhanced by sucrose. It seems that besides phytohormones, other chemicals can also regulate growth and green leaf yield and thus, could have a great potential in the tea industry.